Having Sex, Wanting Intimacy: Why Women Settle for One-Sided Relationships - Weber, Jill P. (Rowman & Littlefield Publishers, 2013)
Finding lasting love and intimacy can be difficult for many women. Some end up agreeing to sexual relationships hoping that they may lead to longer, more fulfilling relationships, only to be let down when they don’t. Here, Jill Weber explains why women feel forced into a male model of dating that barters sex for the unrealistic hope that it will lead to emotional intimacy. What it leads to for the woman, most often, is disappointment, despair, and impaired self-esteem. “Sextimacy,” as Weber terms it, traps women in relationships that are one-sided and lack emotional intimacy. When this happens, women routinely blame themselves instead of realizing they should blame their romantic strategy. This book, in a step-by-step progression, shows a better way to break the cycle and cultivating better relationships. It teaches women how to recognize when they are in a Sextimacy event as opposed to the beginning of a mutually fulfilling relationship that won't leave them racked with morning-after regrets. And it gives clear direction about what women can do to find warm romantic partnerships that serve their needs. Using real stories from women of various ages and stages of life, Weber shows how patterns of behavior may develop that produce a vulnerability to being used. Starting in childhood and proceeding through the crucial teen years, she illustrates the factors that may go into this limited approach to cultivating romantic relationships, and provides clear tips on how to stop. Including a series of self-assessments, the book offers women insight into the patterns that rob them of the opportunities to grow and to fulfill their emotional needs. Anyone struggling to break the cycle of having sex without the attendant intimacy they crave will find in these pages a warm and ready approach to finding love and fulfillment.